Enrichment of semiconducting single-walled carbon nanotubes by simple equipment and solar radiation - Miao, Yuming; Wu, Chuxin; Guan, Lunhui (Nanotechnology, 2019)
High-purity semiconducting (s-) single-walled carbon nanotubes (SWCNTs) have great potential to replace silicon-based materials for microelectronic devices. However, the enrichment methods of s-SWCNTs usually required complex devices and non-renewable energy. In this study, instead of a traditional heating method, renewable solar was employed to dramatically increase the heating rate and improve the reaction to be simple and more controllable, thereby water was successfully used to selectively etch metallic (m-) SWCNTs. In this work, purified SWCNTs films were wetted by water and then exposed to focused solar radiation, causing the surface temperature of the SWCNT films to reach about 800 °C within 2 s. In this case, the m-SWCNTs could be selectively etched by water rapidly. Finally, s-SWCNTs with a purity of about 95 wt% were obtained in several minutes without any complex devices or non-renewable energy.